Do banks benefit from internationalization? Revisiting the market power-risk nexus - Claudia M. Buch; Cathérine Tahmee Koch; Michael Koetter (Deutsche Bundesbank, 2010)
Recent developments on international financial markets have called the benefits of bank globalization into question. Large, internationally active banks have acquired substantial market power, and international activities have not necessarily made banks less risky. Yet, surprisingly little is known about the actual link between bank internationalization, bank risk, and market power. Analyzing this link is the purpose of this paper. We jointly estimate the determinants of risk and market power of banks, and we analyze the effects of changes in terms of the number of foreign countries (the extensive margin) and the volume of foreign assets (the intensive margin). Our paper has four main findings. First, there is a strong negative feedback effect between risk and market power. Second, banks with higher shares of foreign assets, in particular those held through foreign branches, have higher market power at home. Third, holding assets in a large number of foreign countries tends to increase bank risk. Fourth, the impact of internationalization differs across banks from different banking groups and of different size.
Keywords: F3; G21; 330; market power-risk nexus; international banking; micro-data; Germany; Internationale Bank; Marktmacht; Bankrisiko; Bankgeschäft; Globalisierung; Schätzung; Deutschland